EFFECT OF INFORMATION ON ACCOUNTING PROFITS AND CASH FLOW COMPONENTS ON STOCK PRICES OF INSURANCE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (BEI) 2008-2012 PERIOD - Nico Lukito; Kristian Chandra (Universitas Trisakti, 2016)
Many factors influence the fluctuation of stock prices, including: deposit interest rates, stock trading volume, return on equity, earnings per share. The last two factors are part of the financial statements presented by the issuers. The financial statements contain accounting earnings information and cash flow. Therefore it is necessary to examine empirically whether accounting earnings and cash flows have an influence on changes in stock prices. Data is collected from the stock prices of insurance companies that have gone public in the Jakarta Stock Exchange which have a nominal value per share of Rp.1,000.00 (one thousand rupiah) from 2008 to 2012. This study took 10 existing insurance companies to analyze. The basis for this sampling is based on the amount of data available on the Jakarta Stock Exchange Website. From the results of variable analysis of total cash flow and accounting profit variables in the first equation individually can not significantly influence stock prices. And together all the independent variables have no effect simultaneously on stock prices. The value of Squared R is very low, which means that the variable cannot explain stock prices, but can be explained by other variables not included in the research model. Variable operational cash flows, investment cash flows and funding cash flows in the second equation individually can not influence stock prices significantly. And together all the independent variables have no effect simultaneously on stock prices. Also obtained is a very low R Squared value, which means that the variable cannot explain stock prices, but can be explained by other variables not included in the research model